Case report: The histopathological analyses of two myelin oligodendrocyte glycoprotein antibody-associated diseases with a distinctive linear radiating gadolinium enhancement on MRI - Shimizu, Mikito; Beck, Goichi; Murayama, Shigeo; Hoshi, Taku; Sumikura, Hiroyuki; Higashida, Kyoko; Fukasaka, Isao; Shimada, Yuki; Nagashima, Nozomi; Fujioka, Tomohiro; Hatayama, Naoki; Okuno, Tatsusada; et al. (Frontiers in Immunology, 2024)
Myelin oligodendrocyte glycoprotein antibody-associated disease (MOGAD) has highly heterogenous clinical presentations, in which encephalitis is an important phenotype. Moreover, MOGAD has been reported to exhibit diverse imaging findings. However, there have been no previous reports of cases with perivascular radial gadolinium enhancement in periventricular regions, commonly reported in autoimmune glial fibrillary acidic protein (GFAP) astrocytopathy. In this paper, we present two cases of MOGAD with this MRI feature, both of which underwent brain biopsy for the lesions. Brain biopsies revealed perivenous demyelination and inflammation consistent with acute disseminated encephalomyelitis (ADEM), with pronounced axonal damage in Case 1 and minimal axonal involvement in Case 2. Case 1 exhibited more severe cerebral atrophy than Case 2, correlating with the extent of axonal damage. Through these cases, we highlight that the heterogeneity of radiological manifestations of MOGAD, expanding the spectrum beyond previously defined MRI patterns. Furthermore, histopathological analysis revealed distinct axonal involvement as a potential prognostic marker of brain atrophy. These observations emphasize the importance of considering MOGAD in the differential diagnosis, even in cases with atypical imaging findings, and highlight the significance of brain biopsy in guiding both diagnosis and prognosis.